The Effectiveness of Performance Media in Fostering Cultural Awareness and Reflective Consciousness in the Pakat Dayak Community - Brigida Intan Printina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to 1) cultivate cultural awareness of the Pakat Dayak Community through performance media; 2) foster reflective awareness of the journey of the Pakat Dayak Community. Methodology: This research aims to 1) cultivate cultural awareness of the Pakat Dayak Community.This research uses survey methods and a quantitative research approach by delving deeper into the information obtained through questionnaire data collection techniques from a sample representing the Pakat Dayak Community population.through performance media; 2) fostering reflective awareness of the journey of the Pakat Dayak Community Main Findings: The research results indicate that reflective awareness has a significant impact on the effectiveness of the performance media with a regression coefficient value of 0.173 and a significance of 0.002 (<0.05).On the other hand, cultural awareness does not have a significant impact, with a regression coefficient of -0.015 and a significance of 0.818 (>0.05).These findings indicate that performance media are more effective in building cultural understanding when accompanied by critical reflection from the participants. Novelty/Originality of this study: The richness of tradition is a national heritage that needs to be preserved through various means of self-actualization favored by the younger generation.Performance media has become one of the effective means to foster cultural awareness and reflective consciousness, contributing to the development of awareness of the nation's traditions, history, and culture.